Foul play in elite men`s soccer. - Hughes, M.; Cairns, G. (World Congress of Performance Analysis of Sport VIII, 2008)
Fouling is an influential part in football and has the ability to have a hold on the outcome of a match, and whether a team is successful or results in failure. It was found that fouling does affect possession during a match with the team fouled only having a 66% chance of having positive possession. There was also a difference between the amounts of fouls committed by unsuccessful nations compared to successful nations. It was interesting to find that most fouls were committed in centre midfield. There was a high frequency of free kicks given away in attack but this was down to teams applying pressure and from defending from their strikers. The amount of fouls drastically declined the closer you got to their own goal. This was expected as conceding a foul in or around the box could result in your team being punished (E.g. goal, penalty, and direct free kick). During the championships 15 goals were scored from giving away free kicks or penalties in the defending third, which agreed with the findings of Garganta & Sousa (1998), fouling can have a detrimental effect on the performance and result of a match. A particular example of this was England against France. England was winning 1-0 going into 90 minutes when they conceded a free kick outside their box. This was converted which took the score to 1-1. Then a minute later they gave away a penalty by bringing down a striker from France. The end result was 2-1. England had lost the game by committing 2 fouls in the last minutes of the game and got severely punished by losing the game. This shows fouling at its most influential. "Like any other sport, soccer reflects society it is played in. The greater problems of man management and match control created by a more aggressive society, with less respect for authority, are ones which referees must come to terms with." (Ager, 2003, p58) Unfortunately the European Championships only consists of 31 games, so it would be interesting to investigate at the fouling patterns of other tournaments like the World Cup and the Copa America, and also fouling patterns in leagues such as Serie A, the Premier League, and so on. It may be possible define a model for each team to examine where fouls are committed and what players are penalised the most.